Comparative Study on Performance of Discrete Wavelength Transform and Huffman Compression Technique on 2D Signal - Anwar Hussin, Mumtaz; Ahmad Poad, Farhana; Joret, Ariffuddin (Journal of Electronic Voltage and Application, 2021)
Nowadays, the development of technology which involved multimedia data are widely used to help better understanding in spreading information. Image is known as 2D signal which contain huge data especially a high resolution image. In this paper shows the comparison of applying lossy and loss compression on the image data. Image compression is necessary in reducing the size of image for storage or transmission purpose to support most of the application nowadays. Besides, some technique also offers in simplifying the image data to process efficiently. DWT technique and Huffman coding technique are selected as the process of lossy and lossless compression, respectively. The performance of image compression are evaluated in terms of compression ratio, quality of image (MSE, PSNR and SSIM value) and computing time. Several type of evaluation can determine better technique to apply on specific type of application. After conducted a comprehensive observation, DWT technique can provide good performance of compression ratio and computing time as well as the quality of image. Basically, DWT technique only have slight loss of data during the process which the output image is still clear to see by naked eyes. In contrast, Huffman coding technique is lacked in both compression ratio and computing time. However, it helps in maintaining the quality of image without any losses of data. Therefore, certain technique of image compression can be used according to the specific goal of application which depends on the performance of image compression method.